運用問題導向學習設計與實施素養導向教學可行性之探究 The Possibilities of Design and Implementation of Competency-Based Instruction by Using Problem-Based Learning - 張民杰 Min-Chieh Chang (Higher Education Foundation, 2018)
《十二年國民基本教育課程綱要總綱》提倡要培養學生具備素養，以核心素養作為課程設計的主軸。而如何設計與實施素養導向教學，成為推動課程綱要的主要工作。鑑於「問題導向學習」已在許多國家的中、小學實施，是培養學生素養可行的教學方法之一，因此，本研究論述了問題導向學習的發展過程、教材編製、教學步驟、學習成效，並探討其作為素養導向教學的可行性，以作為教師實施與設計素養導向教學之重要參考。 The 12-year national basic education curricula advocate the development of students' competencies. Key competency is the main axis of curriculum design. Designing and implementing competency-based instruction have become the main tasks of the curricula. Problem-based learning is one of the main teaching methods for cultivating student competencies. It has been implemented in primary and secondary schools in many countries. This article discusses the development process, teaching materials, teaching procedures, and learning effectiveness of problem-based learning. This article will also discuss problem-based learning jointed with competency-based instruction, along with providing suggestions for teachers to implement competency-based instruction.